On the invalidity of agricultural real estate acquisition in light of the Act on the shaping of the agricultural system - Blajer, Paweł A. (Przegląd Prawa Rolnego, 2025)
This paper aims to address the issue of the ‘invalidity of agricultural real estate acquisition’ in light of Article 9 of the Act on the shaping of the agricultural system. The considerations presented in this paper reveal numerous flaws in this sanction and justify the urgent need for in-depth reflection on the sanction in the event of a breach of the provisions of the Act on the shaping of the agricultural system. The invalidity of agricultural real estate acquisition seems insufficient to achieve the public law objectives of the Act. On the one hand, it does not ensure the actual effectiveness of the Act’s regulations (e.g. in relation to acts of law other than juridical acts), and on the other hand, it raises doubts as to whether the entire juridical act performed in a manner inconsistent with the Act is invalid, or whether invalid is only its effect in the form of the acquisition of agricultural real estate. Even the very classification of invalidity under the provisions of the Act on the shaping of the agricultural system as absolute invalidity may raise doubts.